Exploring the role of development finance institutions in enhancing the financial and technical capacity of smallholder farmers for agribusiness integration: the case study of Zimbabwe - Hove, Rumbidzai (Graduate School of Business (GSB), 2025)
The economic and social livelihoods of smallholder farmers in Zimbabwe have not improved despite them being holders of land as a key capital resource. Smallholder farmers are still marred with poverty and food insecurity challenges. The purpose of this research is to explore how the economic and social livelihoods of smallholder farmers can be improved to become more sustainable by devising strategies that will enable them to be integrated into the Agribusiness value chain. Helping smallholder farmers transform their farm operations into commercial operations, thereby integrating them into the agribusiness value chain, is the solution that will enable the economic and social livelihoods of smallholder farmers to be transformed. The study seeks to understand the financial and technical capacity challenges that smallholder farmers face and explore how the support of Development Finance Institutions can be leveraged to turn these challenges around. A qualitative approach was employed by conducting discussions with 30 farmers in the Chegutu region of Zimbabwe. The results indicate that farmers face a myriad of challenges that are driven by both external factors and internal factors. Firstly, farmers have significant gaps in their financial capacity caused by inadequate, volatile, and unstable income, and this causes a lack of investment capital, impacting their potential to scale up and increase land utilisation and farm productivity levels. Moreover, the farmers are not deriving sustainable benefits from farm activities, as displayed by the continuous reinvestment into their farms from non-farm income sources. Secondly, farmers have several gaps impacting their technical capacity to drive innovation and efficiencies in their farming operations. This is due to low levels of education and a lack of farm infrastructure. Thirdly, farmers are facing limitations in monetizing their produce in the local agricultural market, which is caused by structural inefficiencies, inability to access markets, and pricing and demand constraints. Lastly, farmers are not getting adequate institutional support to address the capacity challenges. The results from the discussion prompt a call for action; hence, targeted strategies are recommended for DFIs to consider implementing to support the farmers in deriving a financial benefit from their farms through agribusiness development.